2004
DOI: 10.1093/jxb/erh157
|View full text |Cite
|
Sign up to set email alerts
|

The import of phosphoenolpyruvate by plastids from developing embryos of oilseed rape, Brassica napus (L.), and its potential as a substrate for fatty acid synthesis

Abstract: The plastidial phosphoenolpyruvate (PEP)/phosphate translocator (PPT) is expressed in the developing embryos of oilseed rape (Brassica napus L.). PEP can be imported by plastids isolated from embryos and used for fatty acid synthesis at rates that are sufficient to account for one-third of the rate of fatty acid synthesis in vivo. This provides the first experimental evidence for uptake of PEP and incorporation of carbon from it into fatty acids by plastids. PEP metabolism in isolated plastids is able to provi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

2
47
1

Year Published

2006
2006
2020
2020

Publication Types

Select...
5
2
2

Relationship

0
9

Authors

Journals

citations
Cited by 39 publications
(50 citation statements)
references
References 29 publications
2
47
1
Order By: Relevance
“…In Brassicaceae, such as canola (Brassica napus) or Arabidopsis thaliana, PEP is likely to be the predominant precursor for fatty acid biosynthesis in seeds (Schwender and Ohlrogge, 2002;Schwender et al, 2003;Andre et al, 2007, Baud et al, 2007bLonien and Schwender, 2009). Hence, a sufficient provision of PEP appears to be essential for lipid biosynthesis and storage (Kubis et al, 2004). In principle, pyruvate generated by cytosolic PK may be imported as precursor for fatty acid biosynthesis, which is supported by feeding experiments with 14 C-labeled pyruvate to isolated plastids from B. napus embryos and the subsequent incorporation of 14 C into fatty acids (Kang and Rawsthorne, 1994;Eastmond and Rawsthorne, 2000).…”
Section: Introductionmentioning
confidence: 92%
“…In Brassicaceae, such as canola (Brassica napus) or Arabidopsis thaliana, PEP is likely to be the predominant precursor for fatty acid biosynthesis in seeds (Schwender and Ohlrogge, 2002;Schwender et al, 2003;Andre et al, 2007, Baud et al, 2007bLonien and Schwender, 2009). Hence, a sufficient provision of PEP appears to be essential for lipid biosynthesis and storage (Kubis et al, 2004). In principle, pyruvate generated by cytosolic PK may be imported as precursor for fatty acid biosynthesis, which is supported by feeding experiments with 14 C-labeled pyruvate to isolated plastids from B. napus embryos and the subsequent incorporation of 14 C into fatty acids (Kang and Rawsthorne, 1994;Eastmond and Rawsthorne, 2000).…”
Section: Introductionmentioning
confidence: 92%
“…If this transporter is highly abundant and in vivo reversible, the modulation of plastidial PEP levels by PKp can be thought to be propagated across the chloroplast envelope so that the feedback control can take place in the cytosol. Accordingly, the PEP/phosphate translocator has been ascribed an important role in lipid synthesis (Ruuska et al, 2002;Kubis et al, 2004), and its overexpression in tobacco seeds has been demonstrated to promote lipid accumulation (Fuchs et al, 2013).…”
Section: Complexity Of Subcellular Compartmentationmentioning
confidence: 99%
“…Moreover, a previous microarray analysis of Arabidopsis developing seeds has indicated that plastid uptake of cytosolic PEP is a more likely possibility than the uptake of cytosolic pyruvate during seed development (Ruuska et al, 2002), particularly since a plastid pyruvate translocator has yet to be identified. Furthermore, a flux model for central carbon metabolism of developing B. napus embryos constructed based on stable isotope labeling of sugars has also suggested that the main carbon flux into FAs is through plastid uptake of cytosolic PEP (Schwender et al, 2003;Kubis et al, 2004).…”
Section: Proteomics Data Suggest That Phosphoenolpyruvate Is a Directmentioning
confidence: 99%
“…Biochemical and molecular studies are beginning to define the biosynthetic pathways responsible for accumulation of these storage components in B. napus seed (Rawsthorne, 2002;Schwender and Ohlrogge, 2002;Hill et al, 2003;Schwender et al, 2003;Goffman et al, 2004;Kubis et al, 2004;Ruuska et al, 2004;Schwender et al, 2004aSchwender et al, , 2004bChia et al, 2005;Goffman et al, 2005). Recently, a study of B. napus developing embryos demonstrated that Rubisco acts without the Calvin cycle to increase the efficiency of carbon use during triacylglycerol production (Schwender et al, 2004a).…”
mentioning
confidence: 99%